Pengaruh Media Power Point terhadap Motivasi Belajar dan Berpikir Kritis Peserta Didik pada Mata Pelajaran Sejarah Kebudayaan Islam - Hapid Hapid; Paisal Ahmad Akbar; Sheila Mafaizah; Siti Fatmawati; Haedarullah Haedarullah; Munazzah Hurun Ainun; Syahruramadhan Syahruramadhan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
The development of educational technology has encouraged the use of learning media that can improve the quality of teaching and learning processes, including in Islamic Cultural History (ICH) subjects. However, students' learning motivation and critical thinking skills remain significant challenges in ICH learning. This study aimed to analyze the effect of PowerPoint media on students' learning motivation and critical thinking skills in Islamic Cultural History subjects. The research employed a quantitative approach using an Ex Post Facto (causal-comparative) method. The sample consisted of 39 students selected through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, Pearson Product Moment correlation, and simple linear regression with the assistance of SPSS 26. The findings revealed that the use of PowerPoint media positively influenced students' learning motivation and critical thinking skills. Systematic, engaging, and visually supported presentations enhanced students' participation in learning activities, encouraged active engagement, and facilitated deeper understanding, analysis, and evaluation of learning materials. These findings indicate that PowerPoint media can serve as an effective instructional medium for improving both the learning process and learning outcomes in Islamic Cultural History education.